Environmental Knowledge and Environmental Care Attitude Students in State Islamic Senior High School Adiwiyata and Non-Adiwiyata at Banjarmasin City - Nur Mala Sari; Sugeng Utaya; I Komang Astina; Ardyanto Tanjung; Sumarmi Sumarmi (JPG (Jurnal Pendidikan Geografi), 2026)
Environmental issues are happening in Banjarmasin City, therefore it is important to utilize the role and function of schools to educate the younger generation about environmental awareness. The purpose of this research is to measure the level of environmental knowledge and environmental care attitude of students at Adiwiyata schools namely MAN 3 Banjarmasin and Non-Adiwiyata schools namely MAN 1 Banjarmasin, as also to identify school participation in the implementation of the Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (Gerakan PBLHS). This study is a survey research using descriptive quantitative methods through questionnaires filled out by 285 students using random sampling techniques, observation, interviews with teachers and students, and documentation. The data were analyzed using the T-test and analysis of the level of knowledge and attitude towards caring for the environment. The Sig. (2-Tailed) value for Environmental Knowledge was 0.773 and for Environmental Care Attitude was 0.999. This shows that Sig. (2-Tailed) > 0.05, which indicates that there is no difference in the environmental knowledge and care attitude of Adiwiyata and Non-Adiwiyata school students. This is supported by the fact that 92% of MAN 3 Banjarmasin students and 88% of MAN 1 Banjarmasin students have excellent environmental knowledge, while 62% of MAN 3 Banjarmasin students and 67% of MAN 1 Banjarmasin students showed a very caring attitude towards the environment.The Gerakan PBLHS carried out by the two schools was not much different, namely commitment to the vision and mission as one of the school rules to protect the environment, learning that includes environmental issues, greening activities, the existence of a Waste Bank, and environmental cleanliness activities involving the entire school community. In Geography, this research is integrated with Environmental Education in shaping students' knowledge, values, and skills in understanding the impact of human interaction with the environment.